Characterization of Some Leading Mango (Mangifera indica L.) Cultivars in Bihar Condition Based on Yield and Chemical Quality Parameters - Ravindra Kumar; Samik Sengupta; Ankur Kumar Rai; Amit Raj; K.P. Singh; Suman Kumari (Archives of Current Research International, 2024)
A conventional and simple technique to determine the ideal genotype for a breeding program is to characterize various genotypes of mangos according to their yield and chemical quality parameters. In light of this, an inquiry was carried out in the experimental area of BAU, Sabour, with the aim of characterizing a few elite mango cultivars in the agro-climatic conditions of Bihar based on factors related to yield and chemical quality. Using yield and chemical quality characteristics, twenty mango cultivars were characterized in 2008–2009. Fruit set per panicle (12.66 to 72.58 fruits per panicle), number of fruits per tree (284.15 to 784.41 fruits per tree), fruit weight (105.45 to 488.15g), fruit yield (39.67 to 343.68 kg), TSS (15.60 to 21.96 0Brix), total sugar (13.25 to 24.15 percent), reducing sugar (2.20 to 6.92 percent), acidity (0.23 to 0.43 percent), and ascorbic acid (11.49 to 55.22 mg) were among the cultivars that differed most significantly. In the Bihar agro- climatic conditions, Langra surpassed Mallika in terms of fruit quality criterion and Mallika produced a greater yield among the cultivars described below.